Pengaruh Sistem Keuangan Desa, Transparansi dan Sistem Pengendalian Intern Pemerintah (SPIP) Terhadap Akuntabilitas Pengelolaan Dana Desa di Kecamatan Jatipurno Kabupaten Wonogiri - Carolina Novithasari; Setyaningsih SU (Teewan Journal Solutions, 2026)
This study was designed to empirically examine the influence of the village financial system, transparency, and the Government Internal Control System (SPIP) on the accountability of village fund management in the village government of Jatipurno Subdistrict, Wonogiri Regency. The research methodology used was a quantitative survey with primary data sources. A sample of 45 respondents was obtained through purposive sampling, and a questionnaire instrument was used for data collection. Data analysis techniques included multiple linear regression and hypothesis testing (t-test and F-test). The results of the study concluded as follows: (1) The village financial system, transparency, and SPIP individually proved to have a significant effect on the accountability of village fund management. (2) The value of the coefficient of determination (Adjusted R²) was 0.777, indicating that 23.3% of the variation in the dependent variable was explained by the independent variables.